Phytochrome A Protects Tomato Plants From Injuries Induced by Continuous Light - Velez-Ramirez, Aaron I.; Vreugdenhil, Dick; Millenaar, Frank F.; van Ieperen, Wim (Frontiers in Plant Science, 2019)
Plants perceive and transduce information about light quantity, quality, direction and photoperiod via several photoreceptors and use it to adjust their growth and development. A role for photoreceptors has been hypothesized in the injuries that tomato plants develop when exposed to continuous light as the light spectral distribution influences the injury severity. Up to now, however, only indirect clues suggested that phytochromes (PHY), red/far-red photoreceptors, are involved in the continuous-light-induced injuries in tomato. In this study, therefore, we exposed mutant and transgenic tomato plants lacking or over-expressing phytochromes to continuous light, with and without far-red light enrichment. The results show that PHYA over-expression confers complete tolerance to continuous light regardless the light spectrum. Under continuous light with low far-red content, PHYB1 and PHYB2 diminished and enhanced the injury, respectively, yet the effects were small. These results confirm that phytochrome signaling networks are involved in the induction of injury under continuous light.